Combined Anticoagulant Therapy for Prevention of Preeclampsia and Small for Gestational Age Neonates: A Systematic Review and Meta-analysis - Kontovazainitis, Christos-Georgios; Gialamprinou, Dimitra; Katsaras, Georgios N.; Pouliakis, Abraham; Theodoridis, Theodoros; Mitsiakos, Georgios (American Journal of Perinatology, 2022)
Objective This systematic review and meta-analysis (SRMA) aims to compare the efficacy of combining low molecular weight heparin (LMWH) and aspirin against aspirin alone in preventing preeclampsia (PE) and small for gestational age (SGA) neonates in women at moderate and high risks.Study Design The included studies were nonrandomized and randomized clinical trials (RCTs) enrolling women at moderate and high risks for developing preeclampsia. PubMed/Medline, Cochrane Library, Embase, and Grey literature (including ClinicalTrials.gov) were searched.Results Out of 4,762 records, 7 nonrandomized studies and 12 RCTs (enrolling 545 and 1,677 women, respectively) were selected. Although the studies were clinically heterogeneous, the conduction of quantitative analysis was feasible. Regarding RCTs, the odds of early-onset preeclampsia was reduced by 89% (pooled odds ratio [OR] = 0.11, 95% confidence interval [CI]: 0.01–0.93, p = 0.04) in women with thrombophilia, the incidence of SGA neonates below the 5th percentile by 48% (pooled OR = 0.52, 95% CI: 0.28–0.96, p = 0.04) in women with a history of preeclampsia and/or SGA neonates, and the incidence of SGA neonates below the 10th percentile by 31% (pooled OR = 0.69, 95% CI: 0.50–0.96, p = 0.03) in the whole population.Conclusion Concerning the whole studied population, combined anticoagulant therapy is not superior to aspirin alone. However, it may be more effective in preventing early-onset preeclampsia regarding women with thrombophilia, SGA neonates below the 5th percentile regarding women with a history of preeclampsia and/or SGA, and SGA neonates below the 10th percentile in moderate- or high-risk women. The above mixed but promising results need to be envisaged with caution due to the clinical heterogeneity of the included studies which is the main limitation of our research. Nevertheless, the strict and narrow inclusion search criteria, and the appropriate subgroup analysis are its main strengths. More RCTs with homogeneous populations and stricter inclusion criteria are needed to confirm these results.Key Points
Keywords: preeclampsia; small for gestational age; low molecular weight heparin; aspirin